2018
DOI: 10.9771/rc-ufba.v12i2.22514
|View full text |Cite
|
Sign up to set email alerts
|

A Participação Feminina Na Produção Científica Das Áreas De Administração E Ciências Contábeis

Abstract: <p>Este artigo analisa como se caracteriza a participação feminina na produção científica das áreas de Administração e Ciências Contábeis no triênio de 2013 a 2015. Realizou-se um estudo bibliométrico, descritivo e de abordagem qualitativa-quantitativa. A amostra compreendeu 23 periódicos de Qualis A1 a B2, nos quais foram analisados todos os 1724 artigos com, pelo menos, uma participação feminina. Após a análise dos artigos, foram observadas 2740 autoras, as quais compuseram um <em>ranking</em&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 0 publications
2
9
0
1
Order By: Relevance
“…The findings of the research corroborate previous studies that identified, in the areas under analysis, a lower female participation (Amaral et al, 2014;Araújo et al, 2014;De Luca et al, 2014;Morais et al, 2018;Resende et al, 2012;R. M. F. de Souza et al, 2017;J.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The findings of the research corroborate previous studies that identified, in the areas under analysis, a lower female participation (Amaral et al, 2014;Araújo et al, 2014;De Luca et al, 2014;Morais et al, 2018;Resende et al, 2012;R. M. F. de Souza et al, 2017;J.…”
Section: Resultssupporting
confidence: 90%
“…Some bibliometric studies were developed in order to investigate female participation in academic production in the fields of science. For example, Morais et al (2018) analyzed the female participation in 1,724 articles published by 23 periodicals classified as A1 to B2, in the areas of Administration and Accounting Sciences, in the triennium from 2013 to 2015, according to the QualisCapes system. The analysis was through bibliometrics verifying the female participation in front of the male, the historical evolution (or involution) of this participation and the authors who produced the most.…”
Section: Previous Studiesmentioning
confidence: 99%
“…The period covered by the present study (2016-2017) complements a study by Elsevier (2017) analyzing scientific production until 2015. The study also expands the research by Morais et al (2016) who mapped female contributions to management and accounting studies published in specialized journals from 2013 to 2015.…”
Section: Introductionmentioning
confidence: 61%
“…The present investigation was instigated by, on one hand, the rapid and profound changes observed in the contribution of women to scientific research over the past decades (Morais, Cabral, Santos, Pessoa, & Oliveira, 2016), and, on the other, the persistence of gender inequality in the scientific community despite these advances (Santos, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation